Distribution of myofibroblast and tenascin‐C in cystic adventitial disease: Comparison with ganglion. (December 2013) - Hao, Hiroyuki; Ishibashi‐Ueda, Hatsue; Nishida, Naoki; Kawakami, Rika; Tsukamoto, Yoshitane; Tsujimoto, Masahiko; Hirota, Seiichi
<x xml:space="preserve">Abstract</x> Cystic adventitial disease (CAD) is a rare peripheral artery disorder which shows the development of gelatinous cysts in the adventitia. Although several theories for the pathogenesis of CAD have been postulated, the etiology of CAD remains unclear. Histological examination of three CAD cases revealed that these cyst walls were composed of fibrous tissue and lacked both epithelial and endothelial lining. The surfaces of these cysts were partially covered with spindle‐shaped cells, similar to the interstitial cells within the cyst wall. A pool of mucinous material in the adventitia was evident. Distribution of vimentin‐positive spindle‐shaped cells and scattered CD68‐positive oval‐shaped cells in the cyst wall was revealed by immunohistochemistry. A part of vimentin‐positive spindle‐shaped cells demonstrated to be positive for α‐smooth muscle actin, indicating the presence of myofibroblasts in the cyst wall. A focal tenascin‐C‐positive area was observed in the cyst wall of our CAD cases. Presence of two different cell types, proliferation of myofibroblasts and expression of tenascin‐C were consistent with those of cyst walls of 20 surgically resected ganglions. These results suggest that CAD may arise as capsular synovial structures, similar to ganglion cysts.